Development of Professional and Pedagogical Skills of Future Teachers on the Basis of an Innovative Approach - Mirzaeva Zubayda Ashurovna (International Journal on Integrated Education, 2023)
This article describes the conceptual approaches to improving the methodological competence of future teachers and its specific features. It was emphasized that the individual-oriented, activity-oriented and differentiated approaches to determining the components of methodical competence of future teachers are important.